Reactive oxygen species and oncoprotein signaling-a dangerous liaison - Chong, S.; Lai, J.; Eu, J.; Bellot, G.; Pervaiz, Shazib (Mary Ann Liebert, Inc. Publishers, 2018)
© 2018, Mary Ann Liebert, Inc., publishers. Significance: There is evidence to implicate reactive oxygen species (ROS) in tumorigenesis and its progression. This has been associated with the interplay between ROS and oncoproteins, resulting in enhanced cellular proliferation and survival. Recent Advances: To date, studies have investigated specific contributions of the crosstalk between ROS and signaling networks in cancer initiation and progression. These investigations have challenged the established dogma of ROS as agents of cell death by demonstrating a secondary function that fuels cell proliferation and survival. Studies have thus identified (onco)proteins (Bcl-2, STAT3/5, RAS, Rac1, and Myc) in manipulating ROS level as well as exploiting an altered redox environment to create a milieu conducive for cancer formation and progression. Critical Issues: Despite these advances, drug resistance and its association with an altered redox metabolism continue to pose a challenge at the mechanistic and clinical levels. Therefore, identifying specific signatures, altered protein expressions, and modifications as well as protein-protein interplay/function could not only enhance our understanding of the redox networks during cancer initiation and progression but will also provide novel targets for designing specific therapeutic strategies. Future Directions: Not only a heightened realization is required to unravel various gene/protein networks associated with cancer formation and progression, particularly from the redox standpoint, but there is also a need for developing more sensitive tools for assessing cancer redox metabolism in clinical settings. This review attempts to summarize our current knowledge of the crosstalk between oncoproteins and ROS in promoting cancer cell survival and proliferation and treatment strategies employed against these oncoproteins. Antioxid. Redox Signal.